Analisis Laju Debit Sesaat di DAS Tubo Bagian Hilir - Rosmaeni; Aldi; Demma Semu, Yulsan (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2025)
The discharge of a river basin is influenced by several factors such as rainfall, land use or vegetation conditions, soil type, and topography. This study was conducted to determine the magnitude of the instantaneous flow rate of the Tubo River Basin in the downstream section. The instantaneous flow rate was determined using the floatation method. The floatation method is the simplest method that can be done to measure the flow rate by flowing an object that can float on the water surface. This study used a ping pong ball with a distance of 10 m. Discharge (m3/s) can be determined by the formula of the river cross-sectional area (m2) multiplied by the river water flow rate (m/s). The river cross-sectional area is determined by measuring the river width multiplied by the average water depth. Meanwhile, the flow velocity can be determined by calculating the path length divided by the average travel time of the ping pong ball. Measurements were carried out on a straight section of the river and were carried out 10 times in the morning and afternoon. The results showed that the average flow discharge of the Tubo River Basin in the downstream section was 28.18 m3/s. The use of forest land of 15.15 ha is smaller than non-forest land of 249.66 ha, which has an impact on the small discharge rate. Land cover characteristics and low rainfall factors influence the discharge rate.